Effect of spacer length on mesomorphic behaviours of chiral liquid crystal compounds containing (-)-menthyl. Issue 12 (26th September 2018) - Luo, Cong-Cong; Meng, Qing-Lin; Wang, Ji-Wei; Yan, Gui-Yang; Jia, Ying-Gang
ABSTRACT: A homologous series of new chiral liquid crystal compounds, M n BEB ( n  = 4–10), was prepared by covalently linking a chiral (–)-menthyl with biphenyl-benzoate via a dicarboxylic spacer of varying length and parity. A combination of analysis methods, such as FT-IR, 1 H NMR spectra, differential scanning calorimetry (DSC), polarised optical microscopy (POM) and X-ray diffraction was carried out to systematically investigate their phase structures and phase transition behaviours. The length and parity of the flexible spacers has a profound influence on the Tm and Tc and a modest odd-even effect is observed for the chiral liquid crystal compounds M n BEB . Only compound M 4 BEB developed an N* phase with selectively reflection on heating and a blue phase on cooling process. In addition, increasing the length of the flexible spacers tends to narrow the temperature range of the N* phase and widen the smectic phase, moreover, the pitch becomes longer with the spacer increases. GRAPHICAL ABSTRACT: